Immunofluorescent localization of MAPKs in Steedman's wax sections - Ovečka, Miroslav; Samajová, Olga; Baluška, František; Samaj, Jozef (Methods in molecular biology (Clifton, N.J.), 2014)
Signals of different nature are transduced in cells through signal transduction pathways, where mitogen-activated protein kinases (MAPKs) play an important role as signaling molecules. Views into intracellular localization of MAPKs are critical for the understanding of their spatial and temporal functions, like activation-based relocation, compartmentation, or interactions with local substrates. Localization of MAPKs in cells is thus very useful cell biological approach, extending complex mode of cell signaling characterization in plants. Here, we present a method for subcellular immunofluorescence localization of MAPKs using protein- or phospho-specific antibodies, performed on sectioned fixed plant samples. It is based on embedding of samples in the Steedman's wax, a low-melting point polyester wax embedding medium, which maintains high antigenicity of studied proteins. In addition, exposure of dewaxed sections to antibodies allows for their efficient penetration. Altogether, it makes this simple method a good tool in the efficient subcellular localization of diverse proteins, including plant MAPKs.
Keywords: Polyesters; Waxes; vosky; zalévání tkání; transport proteinů; Arabidopsis; Tissue Embedding; Protein Transport; fluorescenční protilátková technika; Microscopy, Fluorescence; polyestery; Fluorescent Antibody Technique; mitogenem aktivované proteinkinasy; Mitogen-Activated Protein Kinases; fluorescenční mikroskopie; Medicago sativa